MOLLUSCUM CONTAGIOSUM WITH CHILDREN: PECULIARITIES OF COURSE AND MODERN APPROACHES TO THERAPY - N. N. Murashkin; A. I. Materikin; E. T. Ambarchyan; R. V. Epishev (Педиатрическая фармакология)
The article deals with the main aspects of the epidemiology and clinical course of molluscum contagiosum with children. Comparative analysis of the effectiveness  of different treatment  methods has been done. Based on the data of multicenter clinical studies, the authors concluded that the high efficiency and good tolerance  of 5% potassium hydroxide solution in the treatment  of molluscum contagiosum with children children.